2022
DOI: 10.1007/s11356-022-20024-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Recent advances in green technology and Industrial Revolution 4.0 for a sustainable future

Abstract: This review gives concise information on green technology (GT) and Industrial Revolution 4.0 (IR 4.0). Climate change has begun showing its impacts on the environment, and the change is real. The devastating COVID-19 pandemic has negatively affected lives and the world from the deadly consequences at a social, economic, and environmental level. In order to balance this crisis, there is a need to transition toward green, sustainable forms of living and practices. We need green innovative technologies (GTI) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(63 citation statements)
references
References 161 publications
0
34
0
1
Order By: Relevance
“…Advanced technologies are being used to unlock new opportunities to revolutionize the way food protein is produced. For example, technological developments and recent advances in green technologies, such as biotechnology, nanotechnology, nonthermal extraction and processing techniques (e.g., pulsed electric field, high pressure processing, and ultrasound) and other Industry 4.0 technologies have enabled the production of protein foods with better nutritional and sensory qualities and reduced energy consumption and gas emissions, from alternative sources, including food wastes and by-products (Bradu et al, 2022;Ozogul et al, 2021). For example, the application of ultrasound was found to provide many advantages (such as enhanced physical stability, improved desirable bacterial fermentation, and reduced pathogenic microorganisms) to plant-based milks (Sarangapany et al, 2022).…”
Section: Drivers For Alternative Proteinsmentioning
confidence: 99%
“…Advanced technologies are being used to unlock new opportunities to revolutionize the way food protein is produced. For example, technological developments and recent advances in green technologies, such as biotechnology, nanotechnology, nonthermal extraction and processing techniques (e.g., pulsed electric field, high pressure processing, and ultrasound) and other Industry 4.0 technologies have enabled the production of protein foods with better nutritional and sensory qualities and reduced energy consumption and gas emissions, from alternative sources, including food wastes and by-products (Bradu et al, 2022;Ozogul et al, 2021). For example, the application of ultrasound was found to provide many advantages (such as enhanced physical stability, improved desirable bacterial fermentation, and reduced pathogenic microorganisms) to plant-based milks (Sarangapany et al, 2022).…”
Section: Drivers For Alternative Proteinsmentioning
confidence: 99%
“…The research focuses have been predominantly given to the technological development of CPS, IoT, AI, big data analytics, blockchain, additive manufacturing, etc., to achieve predictive maintenance, real-time decision-making, smart manufacturing, and better production control and planning. Besides, these technologies are not only used to improve manufacturing processes but are also applied to enhance supply chain management (Fallahpour et al 2021), innovation (Liu and De Giovanni 2019), and sustainable development (Bradu et al 2022). Particularly, recent research has shown great opportunities to improve sustainability and circular economy with the help of Industry 4.0 (Bag et al 2018;Bai et al 2020), for example, reducing waste generation and improving material utilization by adopting a demand-driven small-scale intelligent production process with additive manufacturing (Ford and Despeisse 2016).…”
Section: Reverse Logisticsmentioning
confidence: 99%
“…At present, many scholars have conducted research on Internet development, technological innovation, industrial structure transformation, upgrading, etc., but most of them are about the technological innovation effect of technological innovation on Internet development, the adoption of big data, and the structural adjustment effect of green open innovation (Paunov and Rollo, 2016;Shahbaz et al, 2021;Wang and Yang, 2021;Bradu et al, 2022). According to recent development, green innovation has become a prominent focus for academics and specialists.…”
Section: Literature Reviewmentioning
confidence: 99%